Sistem Informasi Manajemen Mutu Produk Di PT Deltomed Laboratories Wonogiri - Fajar Dwi Septian; Donna Setiawati; Ari Pantjarani (JITU : Journal Informatic Technology And Communication, 2020)
This research is entitled Sistem Informasi Manajemen Mutu Produk Di PT Deltomed Laboratories Wonogiri. This study aims to create a product quality management information system at PT Deltomed Laboratories, facilitate information management & product quality administration, and create efficiency and effectiveness in the process of product quality management for the better. The system development method used in this study is Waterfall where the process starts from Communication, Planning, Modeling, Construction and Deployment. For system design tools using UML diagrams with the Visual Basic programming language and MySQL Database. The results achieved are a product quality management information system that facilitates information management & product quality administration, as well as creating work efficiency and effectiveness in the process of product quality management for the better.